An investigation of the shape of the hoof capsule in hindlimbs, its relationship with the orientation of the distal phalanx and comparison with forelimb hoof capsule conformation. (21st July 2020) - Kalka, K.; Pollard, D.; Dyson, S. J.
Summary: There is limited information documenting hind foot conformation. The objectives of the study were to describe the shape of the hoof capsule of hindlimbs from the lateral aspect in horses of variable breeds, and, within horses, to compare the conformation of the hoof capsule of forelimbs and hindlimbs and determine the orientation of the distal phalanx within the hoof capsule in hindlimbs. Lateral photographs of the fore and hind feet (n = 225) and lateromedial radiographs of the hind feet (n = 29) were obtained. Differences among breed and shoeing status groups were assessed using multivariable mixed‐effects linear regression models. Angular parameters and ratios of linear measurements were compared between fore and hind feet; angular radiological variables and photographic parameters of the hind feet were compared. The mean dorsal hoof wall angle for hind feet (50.9°±3.7°) was smaller than forefeet (51.8°±3.9°) (P = 0.04). The mean heel angles for hind feet (36.4°±9.6°) were smaller than forefeet (40.1°±9.3°; P < 0.001). Dorsal hoof wall (P < 0.001) and heel (P = 0.002) angles were larger in unshod than shod feet. In the hind feet, the dorsal hoof wall was parallel to the dorsal aspect of the distal phalanx. The median angle of the distal phalanx to the horizontal (angle S) was 0.6° (interquartile range: −1.4, 2.3°). There was a positive relationship between angle S and the hoof wall angle (W); each 1° increase in angle S was associated with 0.6° increase in angle W (P < 0.001). Angle S was also positively associated with photographic heel angle; each degree increase in the angle S was associated with 1.8° increase in the heel angle (P < 0.001). It was concluded that the angle of the distal phalanx to the horizontal in hindlimbs is smaller than published values for forelimbs. The orientation of the distal phalanx in hindlimbs is correlated with external characteristics of the hoof capsule.